Controlled Reduction of Carboxamides to Alcohols or Amines by Zinc Hydrides. Issue 15 (5th March 2019) - Ong, Derek Yiren; Yen, Zhihao; Yoshii, Asami; Revillo Imbernon, Julia; Takita, Ryo; Chiba, Shunsuke
Abstract: New protocols for controlled reduction of carboxamides to either alcohols or amines were established using a combination of sodium hydride (NaH) and zinc halides (ZnX2 ). Use of a different halide on ZnX2 dictates the selectivity, wherein the NaH‐ZnI2 system delivers alcohols and NaH‐ZnCl2 gives amines. Extensive mechanistic studies by experimental and theoretical approaches imply that polymeric zinc hydride (ZnH2 )∞ is responsible for alcohol formation, whereas dimeric zinc chloride hydride (H−Zn−Cl)2 is the key species for the production of amines. Abstract : Mix and match : New protocols for controlled reduction of carboxamides to either alcohols or amines were established using a combination of sodium hydride (NaH) and zinc halides (ZnX2 ). Use of a different halide on ZnX2 dictates the selectivity, where the NaH‐ZnI2 system delivers alcohols and NaH‐ZnCl2 gives amines.